2018
DOI: 10.5223/pghn.2018.21.2.111
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Blood Betatrophin Levels in Obese Children with Non-Alcoholic Fatty Liver Disease

Abstract: PurposeThe prevalence of obesity has significantly increased among children and adolescents worldwide and is becoming an important health care problem in parallel with the increased prevalence of obesity pediatric non-alcoholic fatty liver disease. Betatrophin is a newly define hormone that is commonly secreted by liver and plays role in glucose tolerance. This study aimed to investigate the relationship between serum betatrophin levels and non-alcoholic fatty liver disease in obese children.MethodsThe study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
(32 reference statements)
0
3
1
Order By: Relevance
“…The lack of significant difference in the plasma ANGPTL5 levels between normal-weight and overweight children may indicate that ANGPTL5 is a late obesity marker, and therefore, is not present in higher levels in overweight children. Our findings contrast with the few studies that investigated other ANGPTLs family members, namely ANGPTL3 and ANGPTL8 (betatrophin), and reported no differences between normal-weight and obese children 20,24,25 . This suggests that ANGPTL5 could be a specific and a more sensitive marker for childhood as well as adult obesity than ANGPTL3 and ANGPTL8.…”
Section: Discussioncontrasting
confidence: 99%
“…The lack of significant difference in the plasma ANGPTL5 levels between normal-weight and overweight children may indicate that ANGPTL5 is a late obesity marker, and therefore, is not present in higher levels in overweight children. Our findings contrast with the few studies that investigated other ANGPTLs family members, namely ANGPTL3 and ANGPTL8 (betatrophin), and reported no differences between normal-weight and obese children 20,24,25 . This suggests that ANGPTL5 could be a specific and a more sensitive marker for childhood as well as adult obesity than ANGPTL3 and ANGPTL8.…”
Section: Discussioncontrasting
confidence: 99%
“…Specifically, the research found that serum betatrophin levels were substantially higher in overweight patients but not in obese patients ( Guo et al, 2015 ). In contrast, another study disclosed that betatrophin levels were comparable in obese and insulin-resistant as well as in non-obese subjects ( Battal et al, 2018 ), while another study indicated that betatrophin levels in obese were higher than in non-obese people ( Abu-Farha et al, 2016 ). The serum levels of ANGPTL8/betatrophin/lipasin are significantly increased in obese patients compared to lean individuals independently to the present of polycystic ovary syndrome ( Keyif et al, 2020 ).…”
Section: Discussionmentioning
confidence: 93%
“…Specifically, a study on Korean children in 2015 reported no differences in the levels of either ANGPTL3 or ANGPTL8 between normal-weight children and obese children (15). Another study on Turkish children in 2018 could not also demonstrate significant differences in ANGPTL8 levels between obese and non-obese groups (20). An earlier study performed in China reported no differences in circulating ANGPTL8 levels between lean children and overweight or obese children circulating ANGPTL8 concentration was negatively correlated with insulin resistance in obese children and adolescents; they further suggested that ANGPTL8 might act as a potential biomarker for insulin resistance in obese children or adolescents (22).…”
Section: Discussionmentioning
confidence: 97%